MiRNA and LncRNA as Potential Biomarkers in Triple-Negative Breast Cancer: A Review - Volovat, Simona Ruxandra; Volovat, Constantin; Hordila, Irina; Hordila, Dorin-Alexandru; Mirestean, Ciprian Camil; Miron, Oana Tatiana; Lungulescu, Cristian; Scripcariu, Dragos Viorel; Stolniceanu, Cati Raluca; Konsoulova-Kirova, Assia Adrianova; Grigorescu, Cristina; Stefanescu, Cipriana; et al. (Frontiers in Oncology, 2020)
Noncoding RNAs (ncRNAs) include a diverse range of RNA species, including micro RNAs (miRNAs) and long non-coding RNAs (lncRNAs). MiRNAs, ncRNAs of approximately 19–25 nucleotides in length, are involved in gene expression regulation via either degradation or silencing of the messenger RNAs (mRNAs), and have roles in multiple biological processes, including cell proliferation, differentiation, migration, angiogenesis, and apoptosis. LncRNAs, which are longer than 200 nucleotides, comprise one of the largest and most heterogeneous RNA families. LncRNAs can activate or repress gene expression through various mechanisms, acting alone or in combination with miRNAs and other molecules, as part of various pathways. Until recently, most research has focused on individual lncRNA and miRNA functions as regulators and there is limited available data on ncRNA interactions relating to the tumor growth, metastasis, and therapy of cancer, either acting on mRNA alone or as competing endogenous RNA (ceRNA) networks. Triple-negative breast cancer (TNBC) represents approximately 10%–20% of all breast cancers (BCs), and is highly heterogenous and more aggressive than other types of BC, for which current targeted treatment options include hormonotherapy, PARP inhibitors, and immunotherapy; however, no targeted therapies for TNBC are available, partly because of a lack of predictive biomarkers. With advances in proteomics, new evidence has emerged demonstrating the implications of dysregulation of ncRNAs in TNBC etiology. Here, we review the roles of lncRNAs and miRNAs implicated in TNBC, including their interactions and regulatory networks. Our synthesis provides insight into the mechanisms involved in TNBC progression, and has potential to aid the discovery of new diagnostic and therapeutic strategies.